Soil ecotoxicity study of DEHP with respect to multiple soil species. (February 2019) - Kim, Dokyung; Cui, Rongxue; Moon, Jongmin; Kwak, Jin Il; An, Youn-Joo
Abstract: Di (2-ethylhexyl) phthalate or DEHP is classified as an endocrine-disrupting chemical. It is used as a plasticizer and pesticide additive. Moreover, it has a half-life of about 150–300 days. Thus, it is present in the soil environment and soil risk assessments for DEHP are needed. However, a number of studies have focused on the effects of DEHP in a single soil species. In this study, we conducted acute and chronic toxicity testing for DEHP using varied soil species, including plants, earthworms, soil algae, Collembola, and soil nematodes. In the plant toxicity test, no effect was observed at very high concentration except at some endpoints, and no effect was observed in the earthworm toxicity test. However, there were adverse effects on soil algae, Collembola, and nematodes. Notably, in the Collembola assays, the survival of adults decreased significantly at very high concentrations, whereas reproduction was hindered at low concentrations. Similar inhibition of reproduction was noted in the soil nematode assay. This suggests that DEHP has a greater influence on fertility than survival in the adult test species. However, besides hindered reproduction, no effect was observed on soil species at environmentally relevant concentrations. Graphical abstract: Highlights: We observed acute and chronic toxicity of DEHP on eight soil species. In acute assay, low toxicity was noted even at the high concentrations. Chronic effects were observed albeit at unrealistic environmental concentrations. Especially, reproductive effects were noted for collembola and soil nematodes. Reproductive effects persisted even at DEHP concentrations of 10 mg/kg.